Strategi Pengembangan Ekowisata di Kabupaten Kepulauan Yapen Provinsi Papua - Karsudi K; Rinekso Soekmadi; Hariadi Kartodihardjo (Institut Pertanian Bogor (IPB University), 2010)
Yapen Islands Regency has a very potential and feasible capital to be developed as a tourism attraction object. However, its ecotourism management does not optimal because of several constraints such as lacking institutional capacity of ecotourism management, weak attraction management, less spatial planning of tourism, and ineffective promotion and marketing, as well as problems on regional security. This research was conducted to formulate strategies to develop the islands ecotourism. The results showed that most of the tourism attractions (sea, water, and land ecotourism objects) in Yapen were feasible for further development ecotourism attractions. However, some of the potential tourism objects were not yet possible to be developed due to some barriers and constraints, i.e. unsupportive market potential, bad access due to location of the objects, below-standard management and services, poor accommodation, and high similarity with other objects. The research, therefore, recommends that pessimistic strategy should be applied in overcoming the problems. The strategy should be supported by arrangement of the tourism space, development of attractions management, development of promotion and marketing, development of regulations and management in ecotourism organization, and creation of a conducive and secure situation, both within and outside the tourism area.